Kuchnia i dietetyka późnego antyku oraz Bizancjum. Kilka uwag na temat spożycia, sporządzania, przyrządzania, wartości dietetycznych i zastosowań medycznych konserw rybnych w antycznej i bizantyńskiej literaturze greckiej - Kokoszko, Maciej (Acta Universitatis Lodziensis. Folia Historica, 2005)
Although one can venture common sense remarks on the subject of fish preserve consumption, available literary data make any assessment the role of fish preserves in the late antique and Byzantine diet virtually impossible. It can be only inferred that such food was generally considered to be a delicacy and was eaten by the reach. The less affluent could taste it only on special, festive occasions, but such instances were rather far and few between. It appears that fish preserves constituted no staple food whatsoever. moment of their compilation. The Deipnosophists draw on information form the time of Homer on, however, they hardly ever make use of the data chronologically close to the III-rd century AD. Galen relies on Philotimus, Oribasius on Galen or Xenocrates, while Aetius of Amida and Paul of Aegina borrow their doctrines from Oribasius. The data cannot be rectified on the basis of Byzantine lexica due to the dependence of Hesychios and the Book of Suda on ancient tradition, which is, to make it worse, related to the scope of information preserved in, on the one hand, the Deipnosophists, and on the other, the Geoponics. Consequently, the sources represent a fairly homogenous tradition which cannot not be used directly to draw unequivocal conclusions applicable to late Antiquity and Byzantium. The sources give no detailed information on the way fish preserves were produced. Consequently, there is no precise evidence concerning the technology of production. Available information is general and of a limited value. The main source of data are medical treatises. Their authors claim that fish preserves were manufactured mainly from large fish and that it was salt which was made use of to prevent the meat from decoy. There were a number of varieties of fish preserves which differed in their qualities. However, it seems that generally they tended to include some amount of liquid. These characteristics are reflected in numerous descriptions of waterproof containers in which the salt fish products were preserved. Once the salt fish was taken from the brine, it was soaked in water. When salt was removed form the product, the meat could become the main ingredient of a number of dishes. Greek sources testify to all main techniques of preparing the meat. It could be cooked, grilled or stewed. There is no reliable description of the first method. Nonetheless, it can be suggested that the fish was cooked is salty water, which could also contain some extra ingredients, notably, fresh or dry herbs (fennel or leek) and olive oil. Meat was also grilled on the eschara. The meat prepared in the above specified ways was served with mustard, fresh herbs (mainly oregano) or with sauces, the recipes of which have been preserved in the De re coquinaria. Ancient and Byzantine cooks also stewed the meat, usually with some vegetables (for instance, asparagus) or fruit (for instance, wild water melon). All salt fish dishes were accompanied mainly with bread and sometimes with fresh raw vegetable salads or lentil soup. Dieticians considered salt fish a valuable kind of food. It was regarded as relatively nutritious, contributing to digestion, though of a questionable aroma. It tended to dilute thick humours and was characteristic of desiccating qualities. The last two characteristics were discussed at length in medical treatises and widely profited from by ancient and Byzantine medical doctors while prescribing diets and preparing numerous medicines. Salt meat was recommended to prevent results of the existence of unwanted humours in the body and used to cure ulcers, sores and irritations of various kinds.